The Representation of Women’s Role and Position in Taqrib Book: A Discourse Analysis Study (Mazahib, 2020)
AbstractThis article aims at analyzing woman’s role and position in a book of Islamic jurisprudence (fiqh book). It focuses on the discussion of women’s position in domestic and public sphere as written in the fiqh book titled Taqrib. It also explores the relevance of the Taqrib’s contents on women’s role and position in the social context by probing its readers’ awareness. In this qualitative study, the discourse analysis method is used to examine the contents of the book and the context of readers, i.e. prominent teachers of Islamic boarding school (kyai). Although women’s role and position was depicted subordinate to men in several cases of fiqh reasoning (e.g. the authority of father and grandfather in determining marriage for their daughter, the superiority of men over women in being a judge, and so forth) in the Taqrib book, Some kyai were aware of the women’s role and position in the social life equally. Hence, they maintain that the women’s role and position in the domestic and public environment should be recognized. This study thus emphasizes the need to re-read the fiqh reasoning on women’s role and position contextually. Keywords: woman's role and position, fiqh, Taqrib book.